Immunomodulation of Juvenile Pacu, Piaractus mesopotamicus, by Different β(1-3)(1-6)-D glucan Products - Sabioni,Rafael Estevan (2019)
Abstract Stress in intensive fish farming hamper immune function of fish and cause losses by disease outbreaks, a situation that can be minimized, but cannot be completely circumvented, by the use of immunomodulators. Addition of immunomodulators to aquafeeds has thus become a common practice. β-glucan (BG) is one of most studied and effective immunomodulators, aquaculture purposes included. Extracted from cell walls of bacteria, fungi and selected cereals, BG activity depends on the source and extraction methods. This study evaluated effects of two BG products (BG1 and BG2), extracted from Saccharomyces cerevisiae under varying extraction methods and with different immune activity, on the feeding of pacu Piaractus mesopotamicus juveniles. BG1 provided higher leukocytes respiratory activity when fed at 0.5% inclusion for 10 days and 0.1% inclusion for 15 days. Both products seems to cause negative effect on lysozyme concentration and monocytes profile when fed to pacu for 15 days at 0.5% inclusion. Although the results for BG2 did not differ from control (diet devoid of BG), the proximity with the BG1 behavior is a indicative that a commercial product with smaller BG concentration can be effective when more refined technology is used in extraction process.